SIRT4 Is Highly Expressed in Retinal Müller Glial Cells - Wei, Wei; Hu, Piaopiao; Qin, Mengqi; Chen, Guiping; Wang, Feifei; Yao, Shengrui; Jin, Ming; Xie, Zhi; Zhang, Xu (Frontiers in Neuroscience, 2022)
Sirtuin 4 (SIRT4) is one of seven mammalian sirtuins that possesses ADP-ribosyltransferase, lipoamidase and deacylase activities and plays indispensable role in metabolic regulation. However, the role of SIRT4 in retina has not been clearly understood. The purpose of this study is to explore SIRT4’s location and function in retina. Therefore, Immunofluorescence was used to analyze the localization of SIRT4 in rat, mice and human retina. Western blot was used to assess SIRT4 and glutamine synthetase (GS) protein expression at different developmental stages in C57BL/6 mice retina. And further analyses the retinal structure, electrophysiological function and the expression of GS in SIRT4-deficient mice. Excitotoxicity was caused by intravitreal injection of glutamate (50 nmol) in mice with long-term intraperitoneal injection of resveratrol (20 mg/Kg), and then retinas were subjected to Western blot and paraffin section staining to analyze the effect of SIRT4 on excitotoxicity. We show that SIRT4 colocates with Müller glia cells marker (GS and Vimentin). The protein expression pattern of SIRT4 is similar to GS that both increase with development. There is no significant retinal structure and electrophysiological function change in 2 month SIRT4-deficient mice, while the expression of GS is decreased. Moreover, long-term administration of resveratrol can up-regulate the expression of SIRT4 and GS while reduce the retinal injury caused by excessive glutamate. These results suggest that SIRT4 is highly expressed in retinal Müller glia cells and participate in regulating the expression of GS. SIRT4 doesn’t appear to be essential in retinal development but can up-regulate GS protein expression and protect retina from excitotoxicity.